Implementasi Penggunaan Aplikasi My Like di Kabupaten Bone - Warnita; Takdir, Muhammad; Mursak (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
The My Like application is an application designed to manage human resources quickly, efficiently and effectively. In application development, government employees and agencies can access various important information through an application that simplifies the process of managing administrative services by providing alternative solutions that are sent or managed via accounts created quickly, using administrative service technology, this research uses qualitative methods to explain the implementation of the mylike application in Bone district. Qualitative methods are methods that focus on in-depth observations and produce more comprehensive studies. Data collection techniques in this research use library research. The data source for this research is the website, the My Like Bone application is able to improve employee performance and provide accurate information and knowledge that employees need. Based on the results of the analysis with the availability of the My Like Bone application, ASN employees will be increasingly advanced in using increasingly advanced technology, and will simplify all aspects of city and regional management and improve human resource development.